Aspektualitas dalam Cerpen Karangan Siswa Kelas XI SMA Bakti Idhata - Akifah Humaira Salsabila; Annisa Aulia Rahma (Pusat Riset dan Inovasi Nasional, 2024)
Aspectuality is the speaker's point of view about a situation, for example an event, an ongoing event, a recurring event, or the end of an event. This study aims to describe the types of aspectuality in short stories written by class XI students of SMA Bakti Idhata. This research was conducted using descriptive qualitative method. The data in this study are elements of aspectuality in short stories written by class XI students of SMA Bakti Idhata. The data sources in this study were ten short stories written by class XI students of SMA Bakti Idhata. The data in this study were collected using the technique of listening and note-taking documentation. Based on the results of the study, it appears that from ten short stories written by class XI students of SMA Bakti Idhata, there are several types of aspectualities, namely perfective aspectuality, imperfective aspectuality, incoative aspectuality, continuous aspectuality, aggressive aspectuality, and iterative aspectuality. The most dominant aspectuality is the perfective aspect and the futurative aspect.